Perspektif Gender pada Lengger Lanang Banyumas - Sugeng Iman Hartanto (Pascasarjana ISBI Bandung, 2019)
The changes of lengger role is closely related to a shift in the meaning of the role of Lengger by Somakaton Village community as a sacred figure representing Dewi Sri. These issues need to be discussed to find out the link between the role of Lengger Lanang to be Lengger Wadon. The purpose of this study is to determine the public response to the background of Lengger Lanang Dariah, thevalues contained in Lanang Lengger Dariah, and to know the factors that cause social change, and factors in the development of Lengger Banyumasan. The method used is descriptive analytical. The process of data collection is through the study of documentation, observation and interviews. The result shows that the spiritual activities like sin confession, fasting, ritual offering, and meditatingare still done by Lengger Lanang Dariah. Lengger Banyumasan describes the emotional involvement between the Lengger roles so that social change dominates all these activities.Keywords: Lengger Lanang Dariah, Lengger Banyumasan, crossgender